A comprehensive numerical model of a vapour compression refrigeration system equipped with a variable displacement compressor. (5th March 2022) - Li, Zhaohua; Liang, Kun; Chen, Xinwen; Zhu, Zhennan; Zhu, Zhongpan; Jiang, Hanying
Highlight: A comprehensive numerical model of VCR system is presented. An oil-free VCR system using linear compressor was measured to validate the model. Modelling results show a good agreement with measurements with error within ±10%. The model is able to simulate the compressor and heat transfer in heat exchangers. VCR system with linear compressor is able to achieve capacity modulation. Abstract: As one of the most used cooling technologies, vapour compression refrigeration (VCR) has been widely used in domestic cooling, automobile air conditioning, and industrial cooling. Linear compressor can adjust mass flow rate in response to the system requirements to achieve capacity modulation. A numerical model of variable displacement VCR system driven by a linear compressor is presented in this study to study the characteristic of the system, investigate charge impact, and help to optimize VCR system. The model integrates a heat exchanger model, a refrigerant distribution model, and a detailed compressor model. The proposed model is simulated in MATLAB/Simulink. A prototype linear compressor was studied as a case using R1234yf as working fluid in a variable displacement VCR system. Overall, most of the modelling results fall within ± 10 % of the experimental data. The predicted compressor stroke, power consumption, and mass flow rate have Mean Absolute Percentage Errors (MAPEs) of 2.95%, 6.18%, and 7.08%, respectively, while predicted cooling capacity, coefficient of performance, and refrigerant charge have MAPEs of 8.26%, 8.66%, and 6.1%, respectively. The numerical model indicates that a larger compressor stroke tends to have a higher optimal refrigerant charge. The numerical model can be used for future works on low-charge vapour compression refrigeration system design using microchannel heat exchangers and control strategy development for various applications.